Population-based weight loss and gain do not explain trends in asthma mortality in Cuba: a prospective study from 1964 to 2014 - Suárez-Medina, Ramon; Venero-Fernández, Silvia Josefina; Britton, John; Fogarty, Andrew W. (Elsevier, 2016)
Background